A Novel Homozygous In-Frame Deletion in Complement Factor 3 Underlies Early-Onset Autosomal Recessive Atypical Hemolytic Uremic Syndrome - Case Report - Pollack, Shirley; Eisenstein, Israel; Mory, Adi; Paperna, Tamar; Ofir, Ayala; Baris-Feldman, Hagit; Weiss, Karin; Veszeli, Nóra; Csuka, Dorottya; Shemer, Revital; Glaser, Fabian; Prohászka, Zoltán; et al. (Frontiers in Immunology, 2021)
ABSTRACT Background and objectives Atypical hemolytic uremic syndrome (aHUS) is mostly attributed to dysregulation of the alternative complement pathway (ACP) secondary to disease-causing variants in complement components or regulatory proteins. Hereditary aHUS due to C3 disruption is rare, usually caused by heterozygous activating mutations in the C3 gene, and transmitted as autosomal dominant traits. We studied the molecular basis of early-onset aHUS, associated with an unusual finding of a novel homozygous activating deletion in C3. Design, setting, participants, & measurements A male neonate with eculizumab-responsive fulminant aHUS and C3 hypocomplementemia, and six of his healthy close relatives were investigated. Genetic analysis on genomic DNA was performed by exome sequencing of the patient, followed by targeted Sanger sequencing for variant detection in his close relatives. Complement components analysis using specific immunoassays and Western blotting was performed on frozen plasma samples from the patient and mother. Results Exome sequencing revealed a novel homozygous variant in exon 26 of C3 (c.3322_3333del, p.Ile1108_Lys1111del), within the highly conserved thioester-containing domain (TED), fully segregating with the familial disease phenotype, as compatible with autosomal recessive inheritance. Complement profiling of the patient showed decreased C3 and FB levels, with elevated levels of the terminal membrane attack complex, while his healthy heterozygous mother showed intermediate levels of C3 consumption. Conclusions Our findings represent the first description of aHUS secondary to a novel homozygous deletion in C3 with ensuing unbalanced C3 over-activation, highlighting a critical role for the disrupted C3-TED domain in the disease mechanism.